(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
The liver is a vital organ that plays a central role in metabolism, detoxification, and homeostasis. This article examines the functional anatomy of the liver, emphasizing the relationship between its structural organization and physiological functions. Special attention is given to hepatic lobules, blood supply, and cellular composition, including hepatocytes and non-parenchymal cells. The study also explores the clinical significance of liver structure in relation to common hepatic disorders. Understanding the functional anatomy of the liver provides essential insights for improving diagnosis, treatment, and prevention of liver diseases.